To solve the quadratic equation \(2x^2 - 7x - 3 = 0\), we can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
In this equation, \(a = 2\), \(b = -7\), and \(c = -3\).
First, we calculate the discriminant \(b^2 - 4ac\):
\[ b^2 - 4ac = (-7)^2 - 4 \cdot 2 \cdot (-3) \] \[ = 49 + 24 \] \[ = 73 \]
Now, we can substitute \(a\), \(b\), and the discriminant into the quadratic formula:
\[ x = \frac{-(-7) \pm \sqrt{73}}{2 \cdot 2} \] \[ = \frac{7 \pm \sqrt{73}}{4} \]
So, the two solutions for \(x\) are:
\[ x_1 = \frac{7 + \sqrt{73}}{4} \] \[ x_2 = \frac{7 - \sqrt{73}}{4} \]
These are the solutions to the equation \(2x^2 - 7x - 3 = 0\).